Beta-adrenergic receptor blockers and liver cancer mortality in a national cohort of hepatocellular carcinoma patients. (3rd May 2020) - Udumyan, Ruzan; Montgomery, Scott; Duberg, Ann-Sofi; Fang, Fang; Valdimarsdottir, Unnur; Ekbom, Anders; Smedby, Karin E.; Fall, Katja
Abstract: Background: β-adrenergic signaling has been implicated in the pathology of hepatocellular carcinoma (HCC), but the evidence from clinical studies is limited. In this national population-based cohort study, we investigated the possible association of β-adrenergic receptor blockers and cancer-specific mortality among patients with primary HCC diagnosed in Sweden between 2006 and 2014. Methods: Patients were identified from the Swedish Cancer Register ( n  = 2104) and followed until 31 December 2015. We used Cox regression to evaluate the association of β-blockers dispensed within 90 days prior to cancer diagnosis, ascertained from the national Prescribed Drug Register, with liver cancer mortality identified from the Cause of Death Register, while controlling for socio-demographic factors, tumor characteristics, comorbidity, other medications and treatment procedures. Results: Over a median follow-up of 9.9 months, 1601 patients died (of whom 1309 from liver cancer). Compared with non-use, β-blocker use at cancer diagnosis [ n  = 714 (predominantly prevalent use, 93%)] was associated with lower liver cancer mortality [0.82 (0.72–0.94); p = .005]. Statistically significant associations were observed for non-selective [0.71 (0.55–0.91); p = .006], β1-receptor selective [0.86 [0.75–1.00); p = .049] and lipophilic [0.78 (0.67–0.90); p = .001] β-blockers. No association was observed for hydrophilic β-blockers [1.01 (0.80–1.28); p = .906] or other antihypertensive medications. Further analysis suggested that the observed lower liver cancer mortality rate was limited to patients with localized disease at diagnosis [0.82 (0.67–1.01); p = .062]. Conclusion: β-blocker use was associated with lower liver cancer mortality rate in this national cohort of patients with HCC. A higher-magnitude inverse association was observed in relation to non-selective β-blocker use.